Time-varying structural vector autoregressions and monetary policy: A corrigendum - Marco Del Negro; Giorgio Primiceri (Federal Reserve Bank of New York, 2013)
This note corrects a mistake in the estimation algorithm of the time-varying structural vector autoregression model of Primiceri (2005) and proposes a new algorithm that correctly applies the procedure proposed by Kim, Shephard, and Chib (1998) to the estimation of VAR or DSGE models with stochastic volatility. Relative to Primiceri (2005), the correct algorithm involves a different ordering of the various Markov Chain Monte Carlo steps.
Keywords: C11; C15; 330; Bayesian methods; time-varying volatility